If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-7)-(x+19)=2x
We move all terms to the left:
(x-7)-(x+19)-(2x)=0
We add all the numbers together, and all the variables
-2x+(x-7)-(x+19)=0
We get rid of parentheses
-2x+x-x-7-19=0
We add all the numbers together, and all the variables
-2x-26=0
We move all terms containing x to the left, all other terms to the right
-2x=26
x=26/-2
x=-13
| 3x-8+6x+6=5x+7+4x-9 | | -(8y+1)-(-7y-4)=-1 | | (4/7)x=2 | | 9x+5=4x–5 | | 2x^2=49-16 | | -5u=9-4u | | 3x+10=5x-2(x-5) | | -293=-6+36r+1 | | 7(4k-2)-3=207 | | 2(x+6)8x=10x-12 | | 3/2x-5=7x-17/3 | | 7x+4=1x+8 | | 3(v-2)-4v=(v-9) | | 4(-1x)+3x=-2(x+1) | | -5p-6(1-4p)=146 | | -2x+4=4x-14 | | 5(-3-5x)+7x=-87 | | M/10-310m=40 | | $13.50=9+1.5x | | x+7.35=6.5 | | (-3v+-21)+5=14 | | 7b=-5+8b | | 18-(-y)=-34 | | 119=-7x+7-49x | | 5n^2-1.54n+6=142) | | x+4=9x+3 | | –3(v+7)+5=14 | | 8x-8=2x-40 | | 9x+5=x+6 | | -3x+5+4=19 | | 8(6-6x)-1=287 | | 4x+10=25x=3 |